Develop a colour image classification system - Liu, Jun. (2008)
In this report, we study the color image classification problem. Two important characteristics of the color images are texture and color. The classificaiton of color images depends of the features obtained from image. The work presented in this report will be in the texture feature analysis and color feature analysis.